2019
DOI: 10.35757/kis.2019.63.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Single, but not by Choice – On Deprivation of Relationships among Polish Corporate Employees

Abstract: In studying contemporary transformations of social relations and family life, researchers and social theorists have been focused on the increased diversity of forms of bonding, coupling and other interpersonal connections. When single people are discussed, either it is to emphasize the disintegration of their ties and the crisis of the family, or their single life is considered as an identity choice. The aim of this text is to look at the experience of singleness not by choice among contemporary corporate empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…However, it is questionable how well this theory addresses some individuals' inability to change their status. For instance, Rosińska and Gońda (2019) reported that corporation employees in Poland were unable to change their work conditions in order to maintain the romantic relationships which they desired.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is questionable how well this theory addresses some individuals' inability to change their status. For instance, Rosińska and Gońda (2019) reported that corporation employees in Poland were unable to change their work conditions in order to maintain the romantic relationships which they desired.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is not workable for them to escape the obligations or circumstances which prevent them from being in such a relationship. If it was possible to escape or alter their demands substantively, some are anxious to do so (Jain et al, 2001;Rosi nska & Go nda, 2019).…”
Section: Involuntary Singlehoodmentioning
confidence: 99%
See 1 more Smart Citation